Review paperMastocytosis and clonal mast cell activation syndrome - Górska, Aleksandra; Niedoszytko, Marek; Lange, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Mastocytosis is a group of disorders characterized by the abnormal proliferation and accumulation of atypical mast cells (MC) in one or more organs. In the majority of patients the bone marrow is affected. The clinical presentation of this disease is heterogeneous, ranging from asymptomatic to aggressive with fatal prognosis. Symptoms of mastocytosis result from MC-derived mediators and, less frequently, from destructive infiltration of MCs in tissues. The symptoms of mastocytosis include episodes of MC mediator release and anaphylactic reactions. The diagnosis of mast cell activation disorder (MCAD) has been proposed for subjects without skin lesions (such as urticaria pigmentosa) and unexplained anaphylactic reactions who only meet one or two minor criteria for systemic mastocytosis (SM) (so SM cannot be recognized). The presence of both KIT-mutated and aberrant CD25 expression on bone marrow MCs, defined as clonality, occurs in c-MCAD. Those patients lacking both criteria are considered non-clonal (nc-MCAD). Patients with c-MCAD might correspond to indolent systemic mastocytosis (ISM) at the early phase of the disease. Further follow-up of patients fulfilling only one or two minor criteria for SM is required to determine whether they evolve to SM and to detect disease progression. The diagnosis of MCAD is crucial for the treatment of allergy and anaphylaxis, for example for Hymenoptera venom allergy therapy, which is similar to that applied in patients with SM.